2016
DOI: 10.2139/ssrn.2753137
|View full text |Cite
|
Sign up to set email alerts
|

How Do Regulated and Unregulated Labor Markets Respond to Shocks? Evidence from Immigrants During the Great Recession

Abstract: We study wage adjustment during the recent crisis in Italy using a unique dataset on immigrant workers that includes those employed in formal and informal sector. We find that before the crisis immigrants' wages in the formal and informal sectors moved in parallel (with a 15% premium in the formal labor market). During the crisis, however, formal wages did not adjust down while wages in the unregulated informal labor market fell so that by 2013 the gap had grown to 32%. The difference was particularly salient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 103 publications
0
7
0
Order By: Relevance
“…These values are considered to be high (see, for example, Bellows and Miguel 2009, Guriev et al. 2019, Nunn and Wantchekon 2011). Therefore, we conclude that our estimates cannot be attributed to unobserved heterogeneity.…”
Section: Robustness Placebo Tests and Alternative Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are considered to be high (see, for example, Bellows and Miguel 2009, Guriev et al. 2019, Nunn and Wantchekon 2011). Therefore, we conclude that our estimates cannot be attributed to unobserved heterogeneity.…”
Section: Robustness Placebo Tests and Alternative Mechanismsmentioning
confidence: 99%
“…2007, Borjas and Tienda 1993, Fasani 2015, Guriev et al. 2019, Kaushal 2006, Kossoudji and Cobb‐Clark 2002.…”
mentioning
confidence: 99%
“…Other studies looked into the role played by collective bargaining systems in shaping employment and unemployment dynamics (Brändle and Goerke 2018; Bryson and Dale‐Olsen 2008; DiNardo and Lee 2004; Magruder 2012; Martins 2014) as well as employer‐specific wage differentials (Gürtzgen 2009; Martins 2009; Rusinek and Rycx 2013). In general, most empirical studies find that under sector‐level collective agreements, wages are less resilient to economic shocks and more likely to translate into employment adjustments or working hours reductions (Guriev et al 2019; Izquierdo et al 2017; Ronchi and Di Mauro 2017).…”
Section: Representativeness and Collective Bargaining: A Review Of The Evidencementioning
confidence: 99%
“…In terms of employment, such a causal link is not found: whereas informal output behaves procyclically, informal employment behaves acyclically. The latter may indicate that informal labor markets do not adjust in terms of employment status during economic cycles but in terms of wages or working hours (Guriev, Speciale, and Tuccio 2016;Meghir, Narita, and Robin 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it was shown that foreign interest rates are inversely and significantly related to formal job creation but insignificantly related to informal job creation and destruction, resulting in the countercyclicality of the share of informal employment(Leyva and Urrutia 2020).20 For discussions of these arguments, seeGuriev, Speciale, and Tuccio (2016),Loayza and Rigolini (2011), Maloney (2004), and Meghir, Narita, and Robin (2015.…”
mentioning
confidence: 99%